Liver transplantation for alcohol-associated hepatitis. Issue 2 (23rd April 2023) - Durkin, Claire; Bittermann, Therese
Abstract : Purpose of review: Early liver transplantation is emerging as a treatment option for severe alcohol-associated hepatitis refractory to pharmacotherapies. This review outlines the current status of transplantation for alcohol-associated hepatitis and the treatment of alcohol use disorder after liver transplantation. Recent findings: Rates of early liver transplantation for alcohol-associated hepatitis are increasing with significant heterogeneity in practices across the Unites States. Recent studies have demonstrated a substantial survival benefit in patients transplanted for alcohol-associated hepatitis with improved outcomes in early vs. late transplantation, first vs. prior hepatic decompensation, and posttransplant abstinence/delayed relapse vs. early return to alcohol use. Several prediction algorithms have been developed to ascertain patients' risk of alcohol relapse and aid in candidate selection, though data on treatment of alcohol use disorders in transplant recipients remains limited. Summary: Although controversial, early liver transplantation for severe alcohol-associated hepatitis has shown to be a lifesaving intervention. Additional research is needed to evaluate its long-term outcomes, optimize candidate selection, and understand treatment of alcohol use disorder posttransplant.